2014
DOI: 10.1167/iovs.13-13194
|View full text |Cite
|
Sign up to set email alerts
|

The Ocular Surface Phenotype ofMuc5acandMuc5bNull Mice

Abstract: Our results indicate that deleting either the Muc5ac or Muc5b gene is insufficient to create an observable dry eye phenotype on the ocular surface of these mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
(49 reference statements)
2
22
0
Order By: Relevance
“…S4Av). An earlier report has confirmed that goblet cell development is normal in Muc5ac −/− ; Muc5b −/− mice (Marko et al, 2014). Taken together, we believe that MUC2 and MUC5AC are the developing and mature conjunctival goblet cell markers, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…S4Av). An earlier report has confirmed that goblet cell development is normal in Muc5ac −/− ; Muc5b −/− mice (Marko et al, 2014). Taken together, we believe that MUC2 and MUC5AC are the developing and mature conjunctival goblet cell markers, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…These data correlate with data on Muc5AC and 5B null mice in which no infection was noted at the ocular surface (Marko et al, 2014) and on data from Spdef null mice in which no infections were reported in the gut (Gregorieff et al, 2009);(Noah et al, 2010) or respiratory tree(Park et al, 2007); Chen et al, 2009) . Lack of infection in these experimental mice suggests that other components of the mucosal surface such as membrane-anchored mucins, and surface antimicrobials may be sufficient barriers to prevent infection.…”
Section: Goblet Cell Function At the Ocular Surfacesupporting
confidence: 86%
“…High resolution transmission electron microscopy demonstrates a granule membrane and a “filamentous” substructure to the mucin granule content (Fig. 3B), which may reflect the packaging of the large secretory mucin glycoprotein, MUC5AC in humans (Inatomi et al, 1996), or Muc5ac or 5b in mice (Marko et al, 2014), within the granule. Packaging of the very large, heavily O-glycosylated mucins within the mucin granule is dependent on having a high concentration of multivalent cations within the granule (Perez-Vilar, 2007) and disruption of calcium levels in epithelia due to vitamin D receptor knockdown, alters goblet cell mucin levels and mucin granules in the conjunctiva of the mice (Paz et al, 2003).…”
Section: Conjunctival Goblet Cell Structurementioning
confidence: 99%
See 2 more Smart Citations